The Development Of Online Motorcycle Taxi Transportation And Its Impact On Socio-Economic Change - Muhammad Fadhli; Agusmidah, Agusmidah (Penerbit Hellow Pustaka, 2026)
This study aims to determine how social behaviour affects the emergence of online motorcycle taxi technology and the legal protection of online motorcycle taxi drivers vis-à-vis their online transportation partners. The method used in this study is normative with a legislative approach. Legal materials were collected through literature study and then analysed prescriptively. The results of the study show that the influence of online motorcycle taxis has had a significant impact on people's behaviour, both economically and socially. Online motorcycle taxi drivers still receive occupational safety protection by registering as participants in the Employment Social Security Agency (BPJS Ketenagakerjaan) through the Swadaya Proteksi programme organised by online transportation service providers. With this, service providers are not obliged to provide BPJS facilities.